Origins of oligodendrocytes in the cerebellum, whose development is controlled by the transcription factor, Sox9. (May 2016) - Hashimoto, Ryoya; Hori, Kei; Owa, Tomoo; Miyashita, Satoshi; Dewa, Kenichi; Masuyama, Norihisa; Sakai, Kazuhisa; Hayase, Yoneko; Seto, Yusuke; Inoue, Yukiko U.; Inoue, Takayoshi; Ichinohe, Noritaka; et al.
Abstract: Development of oligodendrocytes, myelin-forming glia in the central nervous system (CNS), proceeds on a protracted schedule. Specification of oligodendrocyte progenitor cells (OPCs) begins early in development, whereas their terminal differentiation occurs at late embryonic and postnatal periods. However, for oligodendrocytes in the cerebellum, the developmental origins and the molecular machinery to control these distinct steps remain unclear. By in vivo fate mapping and immunohistochemical analyses, we obtained evidence that the majority of oligodendrocytes in the cerebellum originate from the Olig2-expressing neuroepithelial domain in the ventral rhombomere 1 (r1), while about 6% of cerebellar oligodendrocytes are produced in the cerebellar ventricular zone. Furthermore, to elucidate the molecular determinants that regulate their development, we analyzed mice in which the transcription factor Sox9 was specifically ablated from the cerebellum, ventral r1 and caudal midbrain by means of the Cre / loxP recombination system. This resulted in a delay in the birth of OPCs and subsequent developmental aberrations in these cells in the Sox9-deficient mice. In addition, we observed altered proliferation of OPCs, resulting in a decrease in oligodendrocyte numbers that accompanied an attenuation of the differentiation and an increased rate of apoptosis. Results from in vitro assays using oligodendrocyte-enriched cultures further supported our observations from in vivo experiments. These data suggest that Sox9 participates in the development of oligodendrocytes in the cerebellum, by regulating the timing of their generation, proliferation, differentiation and survival. Highlights: The majority of cerebellar oligodendrocytes are derived from the ventral rhombomere 1. Sox9 regulates the timing of the cerebellar oligodendrocyte progenitor cell generation. Sox9 is required for differentiation and survival of the cerebellar oligodendrocytes.